Etnis Pribumi dan Sosialisme di Amerika Latin - Hikmatul Akbar (Jurnal Paradigma, 2012)
Beginning of the 21stcentury shows the rising of the indigenous people of Latin America. After having colonized by the European for more than five centuries they are now trying to get their political roles back. As to serve the native people and to get position as political leader, they struggle some and others way. Surviving the history, culture and natural environment are done by Indian movement in some Latin American countries. In some other countries, leader of Indian in Latin America prefer to have their struggle through social organizations and political movement. Along with the democracy growth, the idea socialism come to their mind as to unite the spirit of indigenous people as well as poor people across the countries of Latin America.